Strategi Efektif Manajemen Kelas Disiplin dan Prestasi di UKM Silat Universitas Singaperbangsa Karawang - Permana, Hinggil; Renindra, Naila Saniya; Diyaulkamilah, Zahra; Andriani, Tini (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2025)
Effective classroom management strategies are essential for improving discipline and achievement within the Silat Student Activity Unit (UKM Silat) at Universitas Singaperbangsa Karawang (Unsika). These strategies include the implementation of clear rules, positive reinforcement, and the management of a conducive learning environment. Firm yet flexible rules ensure that members understand their responsibilities, while positive reinforcement through rewards or recognition of achievements fosters motivation and enthusiasm. In addition, a supportive learning environment, both in terms of facilities and emotional atmosphere, helps create a sense of comfort and focus during training sessions. The application of varied teaching methods, such as match simulations, group training, or technical discussions, also contributes to increased member engagement. Periodic evaluations of performance and training strategies allow for adjustments to meet the diverse and dynamic needs of the members.These strategies not only enhance technical skills in silat, but also strengthen values such as responsibility, discipline, and integrity. Inspirational leadership from the coach and the ability to build positive interpersonal relationships among members are also key elements. By creating a supportive and collaborative training culture, UKM Silat Unsika can serve as a platform for talent development and character building, shaping students who are highly competitive both on and off campus. Synergy between the coach and members is the main key to building a harmonious, healthy, productive, and sustainable training environment overall.